Phylodynamics for Human Immunodeficiency Virus Prevention: A Miami-Dade County Case Study - Mehta, Sanjay R; Wells, Alan B; Cohen, Colby; Campbell, Angela; Truong, Michelle; Little, Susan J; Chaillon, Antoine (The Journal of infectious diseases, 2025)
To date, human immunodeficiency virus (HIV) molecular epidemiology has been primarily used to identify clusters of related infections (cluster detection and response) and then address interventions to these clusters. Community groups have raised concern regarding cluster detection and response related to privacy and ethical concerns. Here we demonstrate how an alternative approach to HIV molecular epidemiology can provide public health benefit. A limited data set for Miami-Dade County provided by the Florida Department of Health was curated and annotated by neighborhood health district (NBHD) and genetic linkage (using a genetic distance threshold of ≤0.5%) and phylodynamic analyses were performed. Phylodynamic analyses were used to infer viral transmissions into Miami-Dade County and between NBHDs within the county. A total of 7274 HIV sequences from unique persons collected between 1 January 2015 and 31 December 2021 were analyzed, including 50% of the 7894 new diagnoses during this period. The proportion of sequences in local clusters increased over time. Higher ratios of local introductions, compared to viral egress (ie, source of local clusters in other NBHDs) were observed in 3 NBHDs in North Miami (range, 1.9-2.5), suggesting earlier diagnosis, but high numbers of susceptible persons not receiving preexposure prophylaxis. South Dade/Homestead had a low ratio (0.3) of local introductions compared with egress, suggesting later diagnosis and less durable suppression. Phylodynamic and genetic linkage analyses can highlight populations and geographic regions that might benefit more from particular types of HIV prevention interventions. These findings will need to be explored by evaluating the impact of scaling up interventions informed by these analyses.